2005
DOI: 10.1007/s00467-005-1867-z
|View full text |Cite
|
Sign up to set email alerts
|

A founder mutation in the CLCNKB gene causes Bartter syndrome type III in Spain

Abstract: The term "Bartter syndrome" encompasses a group of closely related inherited tubulopathies characterized by markedly reduced NaCl transport by the distal nephron. At present, five different genetic variants have been demonstrated. The majority of patients with so-called classic Bartter syndrome carry inactivating mutations of the CLCNKB gene encoding the basolateral ClC-Kb chloride channel (Bartter syndrome type III). The purpose of this study was to investigate the underlying mutation in cases of classic Bart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 28 publications
(43 reference statements)
1
37
0
6
Order By: Relevance
“…Therefore, although not widely available in Brazil, molecular tools have become increasingly important for the diagnosis of BS. 2,5,6,9 The rational use of molecular biology techniques will certainly improve our understanding of the genetic aspects of BS, allowing an individualized approach to our patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, although not widely available in Brazil, molecular tools have become increasingly important for the diagnosis of BS. 2,5,6,9 The rational use of molecular biology techniques will certainly improve our understanding of the genetic aspects of BS, allowing an individualized approach to our patients.…”
Section: Discussionmentioning
confidence: 99%
“…2,5,6,9,12 The recent study by Brochard et al,2 who investigated mutations in 42 children with BS, is worth mentioning. Most of those children had heterozygous mutations of the KCNJ1 gene (45%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Rodriguez-Soriano et al [12] have reported a homozygous A204T missense mutation in the CLCNKB gene in 10 Spanish patients with clinical and biochemical features of cBS. This mutation has only been detected in Spain and its presence in families from different geographic regions and different ethnic origins suggests a founder effect in the Spanish population.…”
Section: Introductionmentioning
confidence: 99%